2010
DOI: 10.2164/jandrol.109.007849
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Ascorbate and Catalase on Human Spermatozoa During Cryopreservation

Abstract: Human semen cryopreservation in the clinical management of male infertility is complicated by cryodamage to spermatozoa. We aimed to clarify the full pattern of cryodamage and evaluate the protective effects of ascorbate and catalase on cryopreserved spermatozoa. Semen samples were collected from 30 fertile males. Each sample was divided into 6 groups: fresh semen, cryopreserved semen without treatment, and samples cryopreserved with ascorbate (300 or 600 mM) or catalase (200 or 400 IU/mL). Spermatozoa were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
74
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 37 publications
16
74
0
3
Order By: Relevance
“…During the cryopreservation, the plasma and mitochondrial membranes are equally vulnerable; however, the reduction in the motility is associated with problems in the mitochondrial structure. Catalase improved the motility and viability of human sperm, inhibiting DNA damages and protecting the mitochondrial function, indicating that this antioxidant is useful for decrease the ROS levels (LI et al, 2010). Our results could be indicating that some antioxidants used here (as catalase and superoxide dismutase) were a litter more efficient for the mitochondrial protection than other, as showed by the better values of some kinetics parameters.…”
Section: Resultssupporting
confidence: 53%
“…During the cryopreservation, the plasma and mitochondrial membranes are equally vulnerable; however, the reduction in the motility is associated with problems in the mitochondrial structure. Catalase improved the motility and viability of human sperm, inhibiting DNA damages and protecting the mitochondrial function, indicating that this antioxidant is useful for decrease the ROS levels (LI et al, 2010). Our results could be indicating that some antioxidants used here (as catalase and superoxide dismutase) were a litter more efficient for the mitochondrial protection than other, as showed by the better values of some kinetics parameters.…”
Section: Resultssupporting
confidence: 53%
“…107,108 Several studies have also examined the role of antioxidants in protecting sperm DNA from injury following cryopreservation and thawing. Most studies have shown that antioxidants (vitamin C, catalase, resveratrol and genistein) can protect the sperm DNA from oxidative injury during cryopreservation and subsequent thawing [109][110][111][112] ( Table 6). In contrast, Taylor et al reported that the antioxidant vitamin E does not protect sperm DNA during cryopreservation.…”
Section: Role Of In Vitro Antioxidants In Protecting Spermatozoa Frommentioning
confidence: 99%
“…For example, dead spermatozoa or leukocytes in pre-freezing semen detrimentally affect the sperm survival rate and the fertility potential after thawing through the ROS generation process [6]. A number of studies have demonstrated that supplemental addition of antioxidative to cryoprotective medium, e.g., ascorbate or catalase, minimize DNA damage and preserve sperm integrity; however, the benefit of these supplementations is still debated [25,26]. In this study, we hypothesized that sperm preparation before freezing, compared with sperm preparation after freezing-thawing, would improve post-thawed sperm, i.e., sperm motility, sperm vitality and non-apoptotic sperm.…”
Section: Introductionmentioning
confidence: 99%